On directing and dramaturgy : burning the house - Barba, Eugenio (London : Routledge, 2010)
Aims to trace the roots and development of physicality in theatre by combining practical experience of the field with a historical and theoretical underpinning. This book includes a discussion of issues such as the foregrounding of the body, training and performance processes, and the origins of theatre in both play and human cognition.
boek
Keywords: Barba, Eugenio